2020
DOI: 10.1002/adem.201901578
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Strain‐Softening Phenomenon in Al–0.1% Mg Alloy during High‐Pressure Torsion Processing

Abstract: An Al-0.1% Mg alloy is processed by high-pressure torsion (HPT) at room temperature. The Al-0.1% Mg alloy displays strain-softening phenomenon through hardness evolution: the hardness values in the disc center area are higher than at the disc edge area after 1/2, 1, and 3 turns, and the size of the hard region in the disc center gradually reduces as the number of turns increases from 1/2 to 3 turns. The hardness values evolve toward homogeneity along the disc diameters after 5 and 10 turns. Electron backscatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The processed specimens appear to have attained homogeneity after ten HPT processing turns. It is reported in (Huang et al, 2020) that hardness values evolve toward homogeneity along the disc dimeter after five and ten processing turns which seems to be the case in the currently processed Mg-SiC. Fig.…”
Section: Vickers Microhardness Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The processed specimens appear to have attained homogeneity after ten HPT processing turns. It is reported in (Huang et al, 2020) that hardness values evolve toward homogeneity along the disc dimeter after five and ten processing turns which seems to be the case in the currently processed Mg-SiC. Fig.…”
Section: Vickers Microhardness Resultsmentioning
confidence: 54%
“…Larger samples at moderate hydrostatic pressures and HPT turns tend to exhibit coarser grains at the centre than around the edges hence the microhardness values at the center also tend to be lower than at the edges (Al-Zubaydi et al, 2016;Zhilyaev et al, 2007). Other researchers (Huang et al, 2020) have however observed that HPT processed Al-0.1% Mg alloy exhibited lower hardness values at the disc edges than at its center after half, single and three turns, and that the size of the hard region in the disc center reduced as the number of turns increased from half to three turns.…”
Section: Discussionmentioning
confidence: 96%